Does consumer attitudes and perceived behavioral control impact the purchase intention of halal cosmetic products? / Zarith Delaila Abd Aziz and Norashikin Hussein - Abd Aziz, Zarith Delaila; Hussein, Norashikin (Universiti Teknologi MARA, 2021)
Halal cosmetics industry is a fast growing sectors which reflects the recent rise of the Muslim population globally. The demand for halal cosmetic is projected to increase along with a considerable growth in socioeconomic status. Therefore, the purpose of this study is to explore the extent at which female students in one public university in Selangor has been impacted by attitude and perceived behavioral control on their purchase intention of halal cosmetic products. Survey methods and the purposive sampling were used to collect from 119 respondents. The result revealed that attitude has a high impact on female students in forming their purchase intention for halal cosmetic products. Meanwhile perceived behavioral control shows the lowest impact on respondents. The result of this study assists marketing expert and cosmetic manufacturers to design the best marketing initiatives to understand the cues that give impact on consumer purchase intention.